A Framework for Evaluation and Improvement of Open Government Data Quality: Application to the Western Balkans National Open Data Portals. (June 2022) - Raca, Vigan; Velinov, Goran; Dzalev, Stefan; Kon-Popovska, Margita
Open Government Data (OGD) has become a widely employed tool by governments around the world to promote transparent and accountable policy-making. In the context of societal actors' ability to reuse such data, one of the most important features of ODG is its quality. Thus, through this research, we aim to address the level of data quality by introducing a new framework that constantly monitors and evaluates the OGD quality of Western Balkan (WB) National Open Data Portals. The advantage of the proposed framework is the integration on the portal level enabling information exposure about the quality dimension at any time. An additional value of the framework is the ability to provide recommendations with the intention of improving quality issues. The applicability and findings of the proposed framework are not limited to the WB and once contextualized that could be applied to other countries in the Eastern European that face similar data quality challenges.